Вплив нітратів на функціональний стан нирок - Бадьїн, І.Ю.; Гоженко, А.І.; Лєбєдєва, Т.Л. (Медична гідрологія та реабілітація, 2008)
Введение крысам нитратов в дозе 5 мг/100 г массы тела в первые два часа повышает в плазме крови уровень нитритов в 2 раза, а нитратов - в 15 раз. Выведение нитратов происходит почками и возрастает в 15 раз за счет уменьшения их реабсорбции, одновременно с увеличением экскреции нитритов, фосфатов и белка. It has been established that injection of NaN- to the experimental animals (rats) in the doze of 5 mg/100gr of body mass to their increase in blood plasma during first two hours. Increase of nitrates took place at a lesser degree. A body’s adaptation to the administration of nitrates takes place because of their greater renal excretion.